Modeling Rain Attenuation Effect in Free Space Optic Propagation - Abdul Rahman, Kram; Tauffiq, Khirham (2020)
The project is based on analyzing various intensity of rain through the transmission in free space optic (FSO) communication. The idea is to verify how characteristics of rain can affect the FSO communication system. The required software for simulation of this project is Optisys software system. The locations chosen for this project are Kuching and Samarahan. The rain data is officially collected from Malaysia Meteorological Department (MMD). The measurement through simulation using the real parameter from Laserbit system. The result will determine how intensity of rain can impair the link and to find the alternative method to overcome this problem.